2013
DOI: 10.1186/1756-9966-32-33
|View full text |Cite
|
Sign up to set email alerts
|

MTA1 promotes the invasion and migration of non-small cell lung cancer cells by downregulating miR-125b

Abstract: BackgroundThe metastasis-associated gene 1 (MTA1) has been identified as one critical regulator of tumor metastasis. Previously, we identified miR-125b as a downregualted miRNA in non-small cell lung cancer (NSCLC) cell line upon MTA1 depletion. However, the role of miR-125b and MTA1 in the regulation of NSCLC metastasis remains unclear.MethodsStable MTA1 knockdown NSCLC cell lines 95D and SPC-A-1 were established by transfection with MTA1 shRNA. The effects of MTA1 depletion on the expression of miR-125b and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(128 citation statements)
references
References 23 publications
4
124
0
Order By: Relevance
“…They indicated that MTA1 upregulation was closely related to the invasion and metastasis of NSCLC. Following that, several studies were performed to investigate the role and mechanism of MTA1 in lung cancer promotion (24)(25)(26)(27)(28). However, only NSCLC tissues or cell lines were examined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that MTA1 upregulation was closely related to the invasion and metastasis of NSCLC. Following that, several studies were performed to investigate the role and mechanism of MTA1 in lung cancer promotion (24)(25)(26)(27)(28). However, only NSCLC tissues or cell lines were examined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several cell biological studies have applied an siRNA approach for specific knock-down of MTA1 expression and succeeded in reducing cancer cell transformation, proliferation, clonal growth, VEGF expression, invasiveness, and migration [40,84,[86][87][88][89]. Furthermore, at least two microRNAs have been identified that interfere with MTA1 mRNA stabilization and could be used for MTA1 targeting [90,91].…”
Section: Further Perspectives In Targeting Mta1 and Concluding Remarksmentioning
confidence: 98%
“…This suggests that PCA not only induces apoptosis of tumor cells but also prevents them from metastasis, subsequently in this paper we report the possible mechanisms involved. Metastasis-associated gene 1 (MTA1), an integral part of the nucleosome remodeling and histone deacetylation (NuRD) complex, can inhibit the transcription of target genes by recruiting histone deacetylases into the promoter regions of target genes thus inducing histone deacetylation (Li et al, 2013). MTA1 is up-regulated in human tumors (Hofer et al, 2006) and increases the metastatic and invasive potential of carcinoma cells (Hofer et al, 2004;Kumar et al, 2003;Toh et al, 2004;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%